Review of Biological Needs Fulfillment in Human Rights Review in Class IIA Penitentiary Serang - Devi Paramitha; Sulasno Sulasno (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2021)
Married convicts need the right to fulfill their biological needs to maintain mental and physical health as well as their household, and prevent sexual deviant behavior. Indonesian prisons only focus on overcoming overcapacity, and tend to ignore the biological needs of prisoners, especially since the Class IIA Serang prison is mostly inhabited by married inmates. The fulfillment of biological needs is important, but so far this problem has not been facilitated because it is not regulated in regulations. The purpose of this study was to determine the fulfillment of the biological needs of prisoners in the review of human rights for prisoners at the Class IIA Serang Penitentiary and to find out the obstacles and efforts to fulfill the biological needs of prisoners in the review of human rights for prisoners at the Class IIA Serang Penitentiary. This study uses a normative juridical method through a qualitative approach. Data collection techniques used, namely literature study, interviews and observations. The results show that currently the Class IIA Serang Prison is experiencing overcapacity, the provision of a place to fulfill biological needs in the Class IIA Serang Prison is not implemented due to the absence of regulations, but the Class IIA Serang Prison has an alternative to meet the biological needs of its inmates. This writing results in an analysis of the mechanism for fulfilling sexual needs in Correctional Institutions through alternative models of the romance booth and the provision of Family Visiting Leave which is expected to reduce problems in Correctional Institutions.